Biological clock regulation by the PER gene family: a new perspective on tumor development - Chen, Kai; Wang, Yaohui; Li, Dengxiong; Wu, Ruicheng; Wang, Jie; Wei, Wuran; Zhu, Wei; Xie, Wenhua; Feng, Dechao; He, Yi (Frontiers in Cell and Developmental Biology, 2024)
The Period (PER) gene family is one of the core components of the circadian clock, with substantial correlations between the PER genes and cancers identified in extensive researches. Abnormal mutations in PER genes can influence cell function, metabolic activity, immunity, and therapy responses, thereby promoting the initiation and development of cancers. This ultimately results in unequal cancers progression and prognosis in patients. This leads to variable cancer progression and prognosis among patients. In-depth studies on the interactions between the PER genes and cancers can reveal novel strategies for cancer detection and treatment. In this review, we aim to provide a comprehensive overview of the latest research on the role of the PER gene family in cancer.